Croatian into Latin in 1510 : Marko Marulić and the cultural translation of Regum Delmatiae atque Croatiae gesta - Jovanović, Neven, filolog (Array, 2014)
The differences between two medieval versions, whether the Latin Gesta regum Sclavorum or the vernacular Croatian Chronicle, and the humanistic translation of the latter (RDCG) reveal that Marulić attempted to convert his Croatian source into both a more engaging and stylish work and a more convincing story suitable for a refined and educated international readership. It is this goal which suggests that we should understand Regum Delmatiae atque Croatiae gesta as a distinct example of cultural translation, in the sense of Peter Burke, or of cultural shift, as described by Brenda Hosington in her discussion of the ‘domesticating’ additions, omissions, and modifications in Alexander Barclay’s 1509 version (via the Latin) of Sebastian Brant’s Das Narrenschiff (Hosington). To the Latin humanist readership Marulić presents kings and events from a little-known region with a little-known past, and both need to be made meaningful and, above all, significant. To achieve this, Marulić introduced classicizing equivalents for certain military, legal, and religious terms ; he strove to avoid any repetition he found in the source through elegant variation in his vocabulary and phrasing ; and he found anaphoric pairs to embellish the ends of sentences and close them with an emphatic moralizing point. Yet these elements of copia and style were also accompanied, and indeed supported, by Marulić’s condensed Latin syntax, through which he delivered more (and sometimes more accurate) information at a faster pace, typically streamlining the narrative in attempting to make it more coherent. Although reshaping of the sources into the Regum Delmatiae atque Croatiae gesta might be thought of as a predominantly literary undertaking, behind the ostensibly stylistic preoccupations we can sense a multi-layered ideological agenda. Marulić translated the Croatian Chronicle during the years of frantic Croatian and Dalmatian appeals for help and European unity in the face of Ottoman advances, when repeated warnings were issued to the Pope, to Italy, and to German lands, that Croatia was a bulwark of Christianity, that it could be forced to surrender to the Turks, and that its fall would leave wide open the way to Italy and German lands. Furthermore, these were the years of the League of Cambrai, when there were initiatives for returning Dalmatia from Venetian rule to the Kingdom of Hungary and Croatia. In these contexts, a history of Croats as a ‘gens...bonis itaque dominis molesta, improbis autem et arrogantibus mitis’ (‘people...unruly under the good masters, and obedient to the bad and the despotic’ (Marulić 2011, 208)) might possess not merely moral lessons, but political implications as well. Moreover, as Marulić fashioned Croatian warlords and kings in terms more associated with the rulers found in Livy and Sallust, he tacitly asserted a degree of continuity between the culture of the Romans and the culture of the Croatians (as suggested also by the prominence of Salona, the ancient Roman urban centre whose successor was Marulić’s Split). Such continuity of civilization would be understood by a general reading public of humanistic bent—that is, by most people able to read Latin in Marulić’s time. It would itself add credibility to Croatian claims of their rightful place in the culture of Europe and Christianity, and therefore make stronger the case for struggle against the Ottoman Empire. Finally, a translation into Latin is not necessarily intended to influence only international readers. In Croatia and in Dalmatia there were people who read Latin too, people whose reading could have influenced their behaviour, people whose ideas or assumptions or prejudices could have beeen confirmed by seeing them in an authoritative form ; that Marulić, as an acclaimed religious author, is himself a figure of authority is also important here. Croatian feeling of belonging to European and Christian culture had to be strengthened as well.